Specialization in medical biochemistry in the Republic of North Macedonia-future perspectives - Bogdanska, Jasna; Tosheska Trajkovska, Katerina; Topuzovska, Sonja; Cekovska, Svetlana (My University, 2022)
Laboratory profession across Europe still differs in academic background of the specialists in clinical chemistry. In our country, specialists in medical biochemistry/clinical chemistry hold basic education in general medicine (MDs) or pharma- cy (Ms PHs). The length of the graduate studies in general medicine is six years with 360 ECTS, and the length for general pharmacy is five years with 300 ECTS. Few common subjects are studied during graduate studies for both profiles that differ in the ECTS, such as: Chemistry (7 ECTS for MDs and 39,5 ECTS for Ms PHs); Anatomy and physiology (28 ECTS for MDs and 10 ECTS Ms PHs), Biochemistry (12,5 ECTS for MDs and 6 ECTS for Ms PHs), Biophysics (2 ECTS for MDs and 7 ECTS for Ms PHs), Molecular and Cell Biology and Genetics (10 ECTS for MDs and 6 ECTS for Ms PHs); Microbiology (10 ECTS for MDs and 7 ECTS for Ms PHs); Pathophysiology (11,5 ECTS for MDs and 6 for Ms PH); Pharmacology (7 ECTS for MDs and 6 for Ms PHs); Clinical Biochemistry (1,5 ECTS for MDs and 7 ECTS for Ms PHs). The postgraduate training in medical biochemistry, as a monovalent specialization, for both profiles, ranges 4 years. Although the graduate syllabus in pharmacology doesn’t have any clinical subject, the specialization program for both graduate profiles is the same for both profiles, as well as the title, and was succeeded and revised several times after the succession of the former country. Presently, the total length of basic education for both profiles is 10.5 for MDs and 9,5 years respectively, and both profiles are registered in the European Register of Specialists in Laboratory Medicine. The question arising for the perspective vocational training for medical doctors and pharmacists is: do we need different specialization programs for these pro- files, bearing in mind the previous education and the need of our health care system? The opinion of the members of the Department of Biochemistry and Clinical Chemistry (responsible for proposing and creating specialization syllabuses) is that, in our country, we need two different monovalent specializations in clinical chemistry/medical biochemistry, one for medical doctors and one for masters of pharmacy, which will result in two different profiles and responsibilities in the health care system in our republic.
Keywords: specialization; medical biochemistry; clinical chemistry